Faktor-Faktor Yang Mempengaruhi Burnout Pada Perawat Diruang Rawat Inap RS PMC - Ayudytha, Awaliyah Ulfah; Putri, Desta Asherti (Universitas Fort De Kock Bukittinggi, 2019)
Burnout is a prolonged response related to stressors that continue to occur in the workplace where the result is a combination of workers and jobs. Nurse fatigue occurs when nurses work more than 80% of their work time. The purpose of this study was to determine the factors that influence burnout in nurses in the inpatient room of Pekanbaru Medical Center hospital in 2019.This research method was descriptive correlation with cross sectional approach done to 35 respondents. Sampling technique using total sampling method. The analysis used is univariate analysis and bivariate analysis using Chi-square test. The results showed that there was a significant relationship between workload and burnout (p = 0.024) and there was a significant relationship between leadership style and burnout (p = 0.027). Based on the results of these studies, the researchers recommend that the management of Pekanbaru Medical Center Hospital pay more attention to the level of burnout nurses because the performance of nurses plays an important role in patient care.